2008
DOI: 10.1093/cvr/cvn341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia-induced intrauterine growth restriction on cardiopulmonary structure and function during adulthood

Abstract: Our study demonstrated that hypoxia-induced IUGR is associated with the development of chronic cardiopulmonary dysfunction during ageing. The implication of these findings is the potential usefulness of neonatal diagnosis as a predictor of cardiopulmonary outcomes during adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
144
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(166 citation statements)
references
References 31 publications
15
144
7
Order By: Relevance
“…The gene expression of p53 is increased in severe hypoxia (Li et al 1994;An et al 1998;Hammond et al 2002;Fan et al 2009). In addition, severe hypoxia induces IUGR and abortion (Rueda-Clausen et al 2009). However, in our study, IUGR and abortion were not induced by maternal undernutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression of p53 is increased in severe hypoxia (Li et al 1994;An et al 1998;Hammond et al 2002;Fan et al 2009). In addition, severe hypoxia induces IUGR and abortion (Rueda-Clausen et al 2009). However, in our study, IUGR and abortion were not induced by maternal undernutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, blood pressure measurements were performed using aortic cannulas at a relatively young age of 4 months compared to 12 months of age in this thesis. Previously, progressive signs of cardiovascular dysfunction have been reported in rat offspring exposed to prenatal hypoxia, with diastolic dysfunction and pulmonary hypertension emerging between 4 and 12 months of age (Rueda-Clausen et al, 2008). We observed no signs of renal injury in hypoxia-exposed offspring at 4 months of age despite significant pathology present at 12 months, which suggest that ageing is an additional stressor in animals exposed to prenatal…”
Section: Elevated Mean Arterial Pressuresupporting
confidence: 63%
“…In 12-month-old offspring, we observed that prenatal hypoxia increased interstitial cardiac fibrosis in both sexes. Pathological myocardial fibrosis is associated with diastolic dysfunction, and although we did not perform echocardiography in our study, a similar model of prenatal hypoxia (12% oxygen, E15 -birth) showed rat offspring had normal cardiac function at 4 months of age but went on to develop left ventricular diastolic dysfunction and increased ventricular collagen expression by 12 months (Rueda-Clausen et al, 2008). This supports our findings in the mouse, and suggests our hypoxia-exposed animals with elevated diastolic blood pressure may be at risk of diastolic dysfunction and therefore heart failure.…”
Section: Increased Cardiac Fibrosis With Prenatal Hypoxia and High Saltmentioning
confidence: 72%
See 2 more Smart Citations